CCL13 is upregulated in alopecia areata lesions and is correlated with disease severity. Issue 5 (9th March 2021) - Wang, Dan; Xu, Xueming; Li, Xizhe; Shi, Jian; Tong, Xiaoliang; Chen, Jing; Lu, Jianyun; Huang, Jinhua; Yang, Shengbo
Abstract: Alopecia areata (AA) is a multi‐factors disease characterized by non‐scarring hair loss. AA could be classified into three main clinical phenotypes including patchy type AA (AAP), alopecia totalis (AT) and alopecia universalis (AU) based on the severity and areas of hair loss. Recent studies suggested immunological factor was critical in AA, but the precise aetiology and pathogenesis of AA still need exploration. In the work, we screened two gene expression profiles (GSE45512 and GSE68801 ) from Gene Expression Omnibus (GEO). Based on the two data sets, 10 upregulated genes and 107 downregulated genes in AA skin biopsies were identified. CCL13, as one of the remarkably upregulated genes, was found to have potential biological functions in aberrant immune response of AA according to the GO and KEGG analyses. The PPI network showed CCL13 was associated with multiple immune‐related genes. The expression of CCL13 was increased depending on the severity of disease in AA patients. Cytotoxic lymphocytes, T cells and myeloid dendritic cells accumulated remarkably in scalp tissue depending on the severity of AA, and CCL13 was significantly correlated to cytotoxic lymphocytes, T cells and myeloid dendritic cells in AA patients. Our RT‐PCR and ELISA results found CCL13 was upregulated in skin biopsy and serum of AA patients, and the immunohistochemistry (IHC) detection showed CCL13 was expressed by both the hair follicle epithelium and infiltrating immune cells. In conclusion, the upregulated of CCL13 and subsequent immune cell infiltration was related to AA, which could be a promising target for diagnosis and therapy in AA patients.